2006
DOI: 10.1002/app.23446
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxybisphosphonate‐containing polymeric drug‐delivery systems designed for targeting into bone tissue

Abstract: ABSTRACT:The preparation and characterization of a novel polymeric drug-delivery system designed for bone targeting of antineoplastics is described. The system was based on biocompatible poly[N-(2-hydroxypropyl)methacrylamide] carrier containing hydroxybisphosphonate targeting moieties and the model radiotherapeutics 125 I or 111 In or the anticancer drug doxorubicin. The in vitro binding studies with hydroxyapatite as a bone model proved that the system was efficiently adsorbed on this mineral. The systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 20 publications
2
32
2
Order By: Relevance
“…Different drug-delivery systems for several applications bearing a bone targeting moiety have been previously reported. This includes, HPMA copolymer-doxorubicin-hydroxybisphosphonate conjugate [64], HPMA copolymer–alendronate–paclitaxel conjugate [65] and fluorescein-labeled bone-targeted model conjugates for detection purposes bearing 1% loading of ALN or D-aspartic acid (D-Asp 8 ) oligopeptides [33,35,37,6668]. The common denominator of these conjugates was that they all selectively accumulate in bone tissues regardless of relatively low loading percentage of their bone targeting moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Different drug-delivery systems for several applications bearing a bone targeting moiety have been previously reported. This includes, HPMA copolymer-doxorubicin-hydroxybisphosphonate conjugate [64], HPMA copolymer–alendronate–paclitaxel conjugate [65] and fluorescein-labeled bone-targeted model conjugates for detection purposes bearing 1% loading of ALN or D-aspartic acid (D-Asp 8 ) oligopeptides [33,35,37,6668]. The common denominator of these conjugates was that they all selectively accumulate in bone tissues regardless of relatively low loading percentage of their bone targeting moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the amount of adsorbed polymer was affected by the number of targeting moieties as more ligands yielded higher binding avidity. The authors also concluded that there is a need for multiple targeting moieties to ensure that at least one is exposed [40]. Logically then, multiple targeting ligands become more critical as the nanomedicine size increases [41].…”
Section: Targetingmentioning
confidence: 99%
“…in bone metastases and broken/damaged areas [78][79][80]. This is why hydroxybisphosphonate moieties were also proposed for targeting of polymer carriers [81,82].…”
Section: Nanoparticles For Cancermentioning
confidence: 99%
“…• Conjugates of molecularly water-soluble polymers [81,111] and antibodies [54]. Antibodies are biodegradable proteins with both passive and active targeting potential on their own.…”
Section: Nanoparticles For Cancermentioning
confidence: 99%